Stabilizing a class of time delay systems - Oliveira, Vilma A.; Teixeira, Marcelo C. M. [UNESP]; Cossi, Lúcia (Institute of Electrical and Electronics Engineers (IEEE), 2001)
In this paper we consider the problem of stabilizing a class of time delay systems using fixed order controllers. We show that a time delay system in the class considered is stable if and only if a property of interlacing is satisfied. We use an extension of the Hermite Biehler theorem for polynomials along with its analytical characterization to provide a set of stabilizing controllers.